2020
DOI: 10.1177/1057083720933218
|View full text |Cite
|
Sign up to set email alerts
|

Band Directors’ Perceptions of Instrumental Conducting Curricula

Abstract: The purpose of this study was to examine inservice band directors’ perceptions of their undergraduate instrumental conducting curricula. Members ( N = 141) of the Facebook Band Directors Group who had completed undergraduate conducting and rehearsal techniques coursework responded to an online survey. Respondents felt more confident demonstrating technical conducting behaviors versus expressive ones, perceived their instruction in conducting skills superior to their rehearsal skill instruction, and desired add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Based on pilot testers’ feedback, minor wording changes to two prompts were made to increase clarity. This validation process was consistent with previous investigations examining participant perceptions and experiences (Silvey, 2011; Silvey et al, 2020). I did not examine statistical indicators of reliability because I analyzed data using only item-level descriptive statistics, rather than inferential analyses.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Based on pilot testers’ feedback, minor wording changes to two prompts were made to increase clarity. This validation process was consistent with previous investigations examining participant perceptions and experiences (Silvey, 2011; Silvey et al, 2020). I did not examine statistical indicators of reliability because I analyzed data using only item-level descriptive statistics, rather than inferential analyses.…”
Section: Methodssupporting
confidence: 87%
“…Although a focus on response rate alone is common, according to Lance and Vandenberg (2009), when examining statistical power, it is perhaps equally important to consider sample size. Investigations similarly examining band directors’ perceptions have been conducted with comparably sized participant pools (Rickels & Brewer, 2017; Silvey, et al, 2020) and the authors of these studies did not report a response rate. Additionally, no inferential statistics were conducted in this study, only item-level descriptive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…I sent a recruitment post to the Facebook Band Directors Group to invite participants. This closed-membership group represented an ideal sampling based on years of teaching experience, geographic region, and the variety of ensemble size and skill levels taught (Rickels & Brewer, 2017; Silvey et al, 2020). In my recruitment post, I indicated that participants needed to be inservice instrumental music educators and included a question in which participants identified their current status (e.g., inservice educator, retired educator, preservice student, other).…”
Section: Methodsmentioning
confidence: 99%
“…Participants’ teaching experience ranged from 0 to 5 years ( n = 31, 32.29%), 5 to 10 years ( n = 23, 23.96%), 10 to 15 years ( n = 13, 13.54%), and 15 or more years ( n = 29, 30.21%). As cited in previous literature, Facebook’s privacy restrictions make it impossible to determine a response rate (Rickels & Brewer, 2017; Silvey et al, 2020). Of the 96 participants, 53 taught high school in some capacity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation